Theoretical study of the decomposition mechanism of C4F7N. (15th April 2019) - Fu, Yuwei; Yang, Aijun; Wang, Xiaohua; Rong, Mingzhe
Abstract: Investigations into alternative gases to reduce the usage of SF6 have great benefits on global warming issues and the health of maintenance personnel. C4 F7 N is one of the most remarkable replacements for SF6 owing to its good insulating performance, low global warming potential and non-toxicity. The decomposition mechanism of C4 F7 N is important in evaluating the insulation performance but it is still not clear. Therefore, the B3LYP/6-311G(d, p) method in conjunction with transition state theory is used to study the decomposition mechanism of C4 F7 N. Sixteen reactions are found in the decomposition pathways of C4 F7 N. The optimized configurations and harmonic vibrational frequencies of selected species are very consistent with experimental data to verify the method adopted in this paper. The potential energy surface of these reactions are obtained and the reaction mechanisms are analyzed. The rate constants over 300 K–3500 K relevant to the insulation breakdown temperature are computed based on the above quantum chemistry calculations and dominant reactions in different temperature regions are selected. For example, reaction R 5 (C4 F7 N → TS2 → FCN + CF2 CFCF3 ) is the most important reaction leading to the dissociation of C4 F7 N below 600 K, while reaction R 2 (C4 F7 N → C2 F4 CN + CF3 ) takes the place of reaction R 5 over 600 K to 3300 K and reaction R 3 (C4 F7 N → TS1 → CF2 CFCN + CF4 ) becomes dominant above 700 K; reaction R 15 (CF2 CFCNCF3 → CF2 CFCN + CF3 ) plays the major role in the generation of CF3 with the overwhelming contribution rate. The results obtained here are expected to construct a relatively complete C4 F7 N decomposition scheme, including the main byproduct formation processes and to lay a theoretical basis for the investigation of its insulation performance.